Problematics of PAI Teachers and Their Solutions - Khoiruddin, Untung (Didaktika Religia, 2018)
This article discusses the obstacles found by educators who always face problems in education institution. The problem is related to religious education in schools that have not been maximized, so the competence of professional PAI teachers is needed. Teacher professionalism is very important, when the teacher has a profession as a qualified and accommodating educator. The teacher is having a very big responsibility to educate the nation's children. This is based on Law Number 3 of 2004 concerning the National Education System. One of its functions is to produce nationals who are moral, authoritative and have a personality characteristic of akhlaqul karimah. To achieve this, PAI teachers must be able to have high ideas and commitments so that this nation truly embodies a nation that has good moral character.